Effect of modified 45s5 bioglass on physical and chemical properties of bleached enamel - Mahshid Saffarpour; Bahareh Asgartooran; Mohammad Reza Tahriri; Maryam Mohammadi Savadroudbari; Mehdi Khabazkhoob (Universidade Estadual de Campinas, 2019)
Aim: The purpose of this study was to evaluate of the effects of modified 45S5 bioglass (BG) before, after, and during the bleaching procedure with 35% hydrogen peroxide (HP) on the tooth colour change and physicochemical and morphological properties of human enamel. Methods: Forty-two human premolar enamel samples were prepared and randomly divided into six groups as G1: control (deionized distilled water for 20 min), G2: BG (Bioglass suspension for 20 min), G3: HP (hydrogen peroxide 35% for 20 min), G4: BG before HP (Bioglass suspension for 20 min followed by hydrogen peroxide 35%) , G5: BG after HP (hydrogen peroxide 35% followed by Bioglass suspension for 20 min), and G6: BG during HP (Bioglass in hydrogen peroxide 35% suspension for 20 min). The treatment procedure was performed on the whole enamel surface. Colorimetry was done before and after the treatment procedure. Two specimens from each group were selected for morphological analysis with scanning electron microscope (SEM). Microhardness analysis was performed after the treatment procedure and chemical analysis of BG dissolution was done for BG+DDW and BG+HP suspensions. Results: No statistically significant difference in colour was observed among different groups (P= 0.073133) and the yellowness index decreased in all of the four HP groups. The greatest reduction in microhardness occurred in groups HP and BG before HP (P<0.001) while the BG group showed increased microhardness measurements (P<0.001). Statically significant differences in microhardness were found among the groups. Elemental analysis showed significantly increased levels of Ca and P in BG after HP and BG before HP groups when compared to the HP group. Ionic release of BG was significantly greater in HP when compared to DDW. Conclusion: Using BG before HP had a greater protective effect since it increased microhardness more effectively, decreased mineral loss, and retained the integrity of the enamel surface. The HP group had the lowest microhardness and BG during HP showed less protective effects compared to BG before HP.